Postmodernism approach in Islamic jurisprudence (Fiqh) - Ramli, M.A. (IDOSI, 2013)
The history of Islamic jurisprudence (fiqh) has gone through various phases. From the time of the Prophet Muhammad (PBUH), it has continuously become a dynamic force in fulfilling the contemporary needs of the Ummah. After the period of imitation (taqlid), Islamic jurisprudence enters the renewal process (tajdid) in order to rejuvenate Muslim society to the practice of Ijtihad. The emergence of new approach was caused by the changes and developments in human life that spark to the existence of new issues, which their answers cannot be traced in the works of classical fiqh. Accordingly, some would prefer to utilize the postmodernism approach in the process of interpretation of the divine texts in order to get the ruling (hukm). Some of the thinkers and scholars seem to neglect the normative guide in classical Usul al-Fiqh (the principle of Islamic jurisprudence) and tend to formulate new approaches in jurisprudence deciding process such as deconstruction, hermeneutics, limitation theory and double movement theory. Therefore, this article tends to analyze in the frame of new discourse of postmodernism approach in Islamic Jurisprudence (fiqh). This is especially in jurisprudences that are related to gender issues such as polygamy, inheritance and woman's testimony. Eventually, it becomes crucial to critically analyse the postmodern approach in fiqh whether it is in accordance with the provision in the divine scripts and the higher objectives of Shariah. Key words: Islamic jurisprudence, Postmodernism, Gender, Fiqh, Polygamy